# Find the value of equation

If a + b + c = 0, then the value of (a + b – c)^{2} + (b + c – a)^{2} + (c + a – b)^{2} is

- 0
- 8 abc
- 4(a
^{2}+b^{2}+c^{2}) - 4(ab+bc+ca)

**Answer: (1) 0**

**Explanation:-**

**Given-**

a + b + c = 0

Then, a = – (b + c) , b = – (a + c) & c = – (a + b)

Then,

= (a + b + c)^{2} + (b + c – a)^{2} + (c + a – b)^{2
} Put the value of a, b & c

Then, (a + b – a – b )^{2} + (b + c – b – c)^{2} + (c + a – c – a )^{2
} = (0)^{2} + (0)^{2} + (0)^{2 } = 0

Hence, the answer is (1) 0